Butterflies & wild bees: biology teachers' PCK development through citizen science*. Issue 1 (2nd January 2018) - Scheuch, Martin; Panhuber, Tanja; Winter, Silvia; Kelemen-Finan, Julia; Bardy-Durchhalter, Manfred; Kapelari, Suzanne
Abstract: Citizen science is a rapidly growing emerging field in science and it is gaining importance in education. Therefore, this study was conducted to document the pedagogical content knowledge (PCK) of biology teachers who participated in a citizen science project involving observation of wild bees and identification of butterflies. In this paper, knowledge about how these biological methods can be taught to students is presented. After two years in the project, four teachers were interviewed and their PCK was captured in the form of content representations (CoRes) and Pedagogical and Professional-Experience Repertoires (PaP-eRs). These results can help future citizen science projects to link their activities to the school curriculum. But not only success can be reported: although one of the project team's aims was to make the Nature of Science accessible to the teachers and students in the course of the project, the teachers did not take this aspect into account. This paper discusses the possible reasons and proposes various strategies for improving citizen science in the context of school biology learning.